Politik Hukum Terkait Pertanahan (Agraria) Indonesia - Ahmad Muhamad Mustain Nasoha; Muhammad Syauqi; Jhovan Eko Saputra; Abdul Adzim Hilmi Ahmad (Majelis: Jurnal Hukum Indonesia, 2025)
Land law politics in Indonesia plays a crucial role in realizing social justice and sustainable development through fair and sustainable management of agrarian resources. The primary legal foundation governing land matters is Law No. 5 of 1960 on Basic Agrarian Principles (UU Pokok Agraria), which asserts that all land, water, and air spaces are controlled by the state and utilized to the greatest extent for the welfare of the people. However, the implementation of land law politics faces significant challenges, including disparities in land distribution, agrarian conflicts, and misalignment between central and regional policies. Policy changes, such as the introduction of Land Management Rights and Land Banks through the Omnibus Law, add complexity and raise questions about their alignment with UU Pokok Agraria's fundamental principles. Resolving land disputes also becomes a critical issue, necessitating effective and inclusive legal mechanisms. Therefore, comprehensive reform in land law politics is required, encompassing regulatory harmonization, consistent law enforcement, and active public participation, to ensure fair and sustainable land management for the welfare of the people.